Melhoramento da batata para processamento industrial em condições subtropical e temperada do sul do Brasil - Souza, Zilmar da Silva (2010)
Potato is cultivated in subtropical, during spring and autumn, and temperate conditions, during summer, of the Southern area of Brazil. These different growing conditions affect tuber yield and processing quality. The objectives of this work were to select potato clones with high tuber yield and processing quality and adapted to subtropical and temperate growing conditions; and to develop a breeding strategy to early identify superior clones. We made crosses to develop and early select clones adapted to two growing seasons. Advanced clones were selected for adaptation to subtropical and temperate conditions of the Southern region of Brazil. Yield per hill, tuber appearance, chip color and dry matter and reduced sugar content were evaluated in all experiments. The experiments were a factorial (clones x seasons) in a complete random design, with two or three replications. The highest yield per hill was gotten during summer season of template conditions. Tuber appearance was not affected by season and site growing conditions. The unfavorable conditions of autumn resulted in dark chip color and high content of reduced sugars. Dry matter content varies among environments, but the lowest content was during autumn season. High genetic variability was gotten for all evaluated traits, which enable to select clones better than the check varieties. The first clonal selection should be done during summer season to identify potential clones adapted to subtropical and temperate conditions. Autumn growing conditions are not favorable to high yield and quality and increase dormancy period of the tubers, but this kind of environment is necessary to select clones adapted to two seasons. The clones SJSM01274-4, SJSM01212-2, SJSM00211-3, SJSM99159-8 and SJSM03478-37 have high yield and processing quality in both subtropical and temperate conditions of the Southern area of Brazil.